FORMULATION OF SLOW-RELEASE NPK DOUBLE- COATED GRANULES USING BIOBLEND POLYMER BY SPRAY - & et al., Djamaan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The slow-release NPK double-coated granules obtained was evaluated in term of chemical interaction, surface morphology, and release rate of phosphate by Fourier Transform Infra Red spectrophotometer, Scanning Electron Microscope, and Visible spectrophotometer. Results showed that the FTIR spectrum of granules showed that no chemical interaction was observed between NPK granules and coating polymers during the coating process. The bioblend polymer used was effective as a coating materialfor the slow-release double-coated NPK. The SEM micrograph showed the clearly different part between core and coating polymers. The percentage of phosphate released after 48 hours through the slow-release double and one coated NPK granules were 21.89, and 39.13%, respectively. While through un-coated NPK granules was 93.60%. The release profile of phosphate through slow release double coatedNPK granules was following the Langenbucher kinetics (r = 0.9015).